Bilateral olfactory dysfunction in early stage treated and untreated idiopathic Parkinson's disease. Issue 2 (February 1992) - Doty, R L; Stern, M B; Pfeiffer, C; Gollomp, S M; Hurtig, H I
Abstract : Decreased olfactory function is among the first signs of idiopathic Parkinson's disease (PD). Whether such dysfunction is present to the same degree on both sides of the nose, however, is unknown. Furthermore, whether the deficit results from or is influenced by anti-Parkinsonian medications has not been definitely established. Odour identification ability was evaluated on the left and right sides of the nose in 20 early-stage untreated PD patients, 20 early-stage treated PD patients, and 20 controls. In all cases, the PD related olfactory dysfunction was bilateral and no difference was observed between the test scores of patients taking or not taking drugs for PD. Although asymmetries of unsystematic direction were present in the test scores of some PD patients, similar asymmetries were observed in the controls and the asymmetries were not related to the side of the major motor dysfunction. As in earlier work, no relation was present between the olfactory test scores and the degree of tremor, rigidity, bradykinesia, or gait disturbance at the time of testing. These findings indicate that the olfactory dysfunction of early stage PD is robust, typically of the same general magnitude on both sides of the nose, and uninfluenced by anti-Parkinsonian medications.